PENGARUH JOB INSECURITY DAN KEPUASAN KERJA TERHADAP TURNOVER INTENTION PADA KARYAWAN PABRIK KERAMIK DI MOJOSARI - Nassrulloh, Nassrulloh; Ambarwati, Titik; Mursidi, Mursidi (Jurnal Ilmu Manajemen, 2018)
This study aims to describe the impact of job insecurity and job satisfactionon employee turnover intention at ceramic factory in Mojosari and to figureout the most dominant variable that influences employee performance. Thesample consisted of 68 employees of production department selected byusing Proportionate Stratified Random Sampling technique. In order to pointout the level of job insecurity, job satisfaction, and employee turnoverintention, this study used Likert Scale analysis. Further, Multiple LinearRegression analysis was used to figure out the impact of job insecurity andjob satisfaction on employee turnover intention. The findings indicated thatemployee turnover intention was very high, job insecurity was high, and jobsatisfaction was moderate. Job insecurity did not influence employeeturnover intention with the value of t- arithmetic of 1.051 that is lower than ttableof 1.998. Meanwhile, job satisfaction negatively and significantlyinfluenced employee turnover intention with t-count of -3.108. The result ofSimple Linear Regression analysis, job insecurity and job satisfactionsignificantly influenced employee turnover intention. Moreover, bycomparing the regression coefficients, the most dominant variableinfluencing employee turnover intention was job satisfaction.